Կոմիտաս վարդապետը և ռուսական մշակույթը (հոդված առաջին) - Լուսինե Սահակյան (ՀՀ ԳԱԱ հրատ.)
Данная статья посвящена взаимоотношениям основоположника армянской национальной композиторской школы Комитаса с русской культурой. The article is dedicated to the relationships of Archimandrite Komitas, the founder of the Armenian national composing tradition, with Russian culture.
Keywords: Literature of music